Catalisadores a base de Pt suportados em matrizes mesoporosas de carbono visando a reação de eletrooxidação de glicerol - Andrade, Renato Nunes de (2018)
This work aimed the synthesis, characterization and electrochemical tests of Pt and Pt-Sb nanoparticle catalysts onto mesoporous carbon applied to glycerol electrooxidation reaction. Specifically, the carbon matrixes were synthetized from Si templates with distinct geometries, giving CMK-3 and CMK-5 3D structures. These structures were treated in O2-free atmospheres at 1173 K for 5 h and after the removal of Si with HF solution (as confirmed by thermogravimetric analysis), the mesoporous structures were attested by Small Angle X-Ray diffraction and a 4.8 and 5.3 nm porous diameters were estimated by nitrogen adsorption isotherms to the CMK-3 and CMK-5 structures, respectively. Pt nanoparticles synthesis onto carbon structures (Pt/C) were performed by direct reduction of chloroplatinic acid (H2PtCl6) with formic acid giving particles with 4.5 nm mean diameters as reveled by transmission electron microscopy. Finally, Pt-Sb/C catalysts were produced by irreversible Sb2O3 adsorption. Pt/C catalysts showed voltammetric profiles consistent with metallic Pt in 0.5 mol L-1 H2SO4 solutions, certifying the synthesis success. In the presence of glycerol, it was observed that the activity to the oxidation happens at potential higher than 0.8 V regardless the carbon support; on the other hand, Pt-Sb/C shifted the reaction onset in ca -0.3 V and maintained this activity under fixed potential (0.5 V). Pt-Sb/CMK-3 depicted the best activity among the synthetized catalysts, providing currents 1.6 and 2.0 times bigger than those in Pt-Sb/CMK-5 and Pt-Sb/Vulcan, respectively.